Infeksi COVID-19 pada pasien myasthenia gravis: sebuah tinjauan pustaka - Made Ratna Dewi Setiawan; I Ketut Sumada (DiscoverSys Inc., 2021)
Coronavirus disease (COVID-19) has rapidly become a global pandemic and during this condition, there might be at greater risk of exacerbation in patients with myasthenia gravis. This is related to the viral infection that has been known to increase the risk of a myasthenic crisis. In addition, some experimental drugs used in COVID-19 has been reported to increase the risk of exacerbation in patient with myasthenia gravis. In the other hand, several studies show higher morbidity and mortality rates due to COVID-19 in patient with myasthenia gravis. Myasthenia gravis might be a risk factor for severe COVID-19 infection due to several mechanisms, such as the effect of the immunosuppressive therapy and the inherent respiratory muscle weakness and vulnerabilities. The comprehensive study based on several case report is needed to respond the needs of adaptation in treating patient with myasthenia gravis during this pandemic era. Coronavirus disease (COVID-19) telah menjadi pandemi global dalam waktu singkat. Selama pandemi ini, terdapat peningkatan resiko eksaserbasi pada pasien dengan myasthenia gravis. Hal ini terjadi karena sejak lama telah diketahui bahwa infeksi virus dapat meningkatkan resiko krisis myasthenia pada pasien myasthenia gravis. Beberapa obat eksperimental yang diberikan pada pasien dengan infeksi COVID-19 juga dilaporkan memiliki resiko yang tinggi dalam menimbulkan eksaserbasi gejala myasthenia gravis. Di sisi lain, beberapa studi terkait COVID-19 menunjukkan angka morbiditas dan mortalitas yang lebih tinggi pada pasien dengan myasthenia gravis. Myasthenia gravis juga merupakan faktor resiko untuk infeksi COVID-19 berat yang berhubungan degan beberapa mekanisme seperti efek dari terapi imunosupresan dan kondisi kelemahan otot pernafasan pada penyakit myasthenia gravis. Telaah yang komprehensif berdasarkan beberapa laporan kasus terkait infeksi COVID-19 pada pasien myasthenia gravis sangat diperlukan untuk melakukan adaptasi manajemen terapi pada era pandemi ini.